Glut-1 Deficiency Syndrome and Familial Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
A family with autosomal dominant Glut-1 deficiency syndrome (DS) affecting 5 members over 3 generations is reported from the University of Goettingen, Germany; and Columbia University, New York.